2018
DOI: 10.1111/tpj.13868
|View full text |Cite
|
Sign up to set email alerts
|

A BAHD acyltransferase catalyzing 19‐O‐acetylation of tabersonine derivatives in roots of Catharanthus roseus enables combinatorial synthesis of monoterpene indole alkaloids

Abstract: While the characterization of the biosynthetic pathway of monoterpene indole alkaloids (MIAs) in leaves of Catharanthus roseus is now reaching completion, only two enzymes from the root counterpart dedicated to tabersonine metabolism have been identified to date, namely tabersonine 19-hydroxylase (T19H) and minovincine 19-O-acetyltransferase (MAT). Albeit the recombinant MAT catalyzes MIA acetylation at low efficiency in vitro, we demonstrated that MAT was inactive when expressed in yeast and in planta, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…In marked contrast, both (+)‐minovincinine (Figure , inset lane 8) and its O ‐acetylated derivative (+)‐echitovenine (Figure , inset lane 9) accumulated, but not (+)‐vincadifformine (Figure , inset lane 7). While enantiomeric forms of the MIAs were not specified, hairy roots, adventitious roots and roots from whole C. roseus plants (Carqueijeiro et al ., ,b) were reported to accumulate tabersonine and lochnericine together with lower levels of hörhammericine, vincadifformine, minovincinine and echitovenine, while only traces of 19‐hydroxytabersonine, 19‐ O ‐acetyltabersonine or 19‐ O ‐acetylhörhammericine were detected.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In marked contrast, both (+)‐minovincinine (Figure , inset lane 8) and its O ‐acetylated derivative (+)‐echitovenine (Figure , inset lane 9) accumulated, but not (+)‐vincadifformine (Figure , inset lane 7). While enantiomeric forms of the MIAs were not specified, hairy roots, adventitious roots and roots from whole C. roseus plants (Carqueijeiro et al ., ,b) were reported to accumulate tabersonine and lochnericine together with lower levels of hörhammericine, vincadifformine, minovincinine and echitovenine, while only traces of 19‐hydroxytabersonine, 19‐ O ‐acetyltabersonine or 19‐ O ‐acetylhörhammericine were detected.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained with the T3O homolog showed that these two separate enzymes, sharing 27% amino acid identity, are specific for enantiomer‐specific hydroxylation of (+)‐ and (−)‐aspidosperma skeletons, respectively (Figure ). The results suggest that while 19‐ O ‐acetylhörhammericine is derived from (−)‐tabersonine (Figure ) (Carqueijeiro et al ., ,b), formation of (+)‐echitovenine involved a separate two‐step pathway from (+)‐vincadifformine (Figure ). The T3O homolog that catalyzes this regiospecific and stereospecific hydroxylation was named (+)‐vincadifformine 19‐hydroxylase (V19H).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations